NPR1-like genes in Theobroma cacao: Evolutionary insights and potential in enhancing resistance to Phytophthora megakarya. - Muhammad Umar Rasheed; Aiman Malik; Muhammad Zeshan Haider; Adnan Sami; Muhammad Shafiq; Qurban Ali; Muhammad Arshad Javed; Ansar Ali (PLoS ONE)
Nonexpressor of pathogenesis-related 1 (NPR1) is crucial for activating the plant immune system through the signaling molecule salicylic acid (SA), which triggers systemic acquired resistance (SAR) in Arabidopsis. In this study, three putative genes associated with NPR1 from Arabidopsis have been identified in the genome of Theobroma cacao, namely, TcNPR1, TcNPR2, and TcNPR3, suggesting a functional diversification among the three gene entities. Phylogenetic analysis revealed that TcNPR1 and TcNPR2 branched alongside their Arabidopsis orthologs, NPR1 and NPR2, indicating that these genes maintain a conserved role in SA signaling pathways across different species. In contrast, TcNPR3 exists in a separate clade, suggesting unique functional roles and evolutionary divergence. A comparative analysis of the physiochemical properties of these TcNPRs showed a different subcellular localization, as TcNPR1 persists in the cytoplasm, while TcNPR3 is found in the nucleus, aligning with its proposed role in SA signaling and transcriptional regulation. Furthermore, we identified microRNAs that target TcNPR3, suggesting that P. megakarya may exploit the transcriptional regulatory network to bypass plant defense activation. Transient overexpression or suppression of TcNPR gene expression through RNA interference-mediated gene silencing could be sufficient to study the impact on the production of other molecules, such as SA, some PR protein expressions, and resistance against P. megakarya. The interactions between proteins encoded by TcNPRs and cellular proteins of P. megakarya will provide insight into whether the pathogen manipulates host defenses. Finally, the expression of TcNPR genes in response to infection by P. megakarya offers valuable information regarding the temporal and spatial activation during the defense response.